2008
DOI: 10.1172/jci33637
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine 5 receptor mediates Ang II type 1 receptor degradation via a ubiquitin-proteasome pathway in mice and human cells

Abstract: Hypertension is a multigenic disorder in which abnormal counterregulation between dopamine and (1-4). The D 5 R is widely expressed in the rodent kidney, specifically in the proximal and distal tubules, cortical collecting ducts, medullary ascending limbs of Henle, and arterioles, but not in the glomeruli, juxtaglomerular cells, or macula densa (5). The AT 1 R is also widely expressed in the kidney, specifically in the proximal and distal tubules, cortical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 55 publications
3
70
1
Order By: Relevance
“…Thus, dopamine and ANG II appear to serve counterregulatory functions in the kidney (5,15,16). In this regard, dopamine inhibits renal renin expression (38) and inhibits ANG II-mediated tubule function and AT 1 expression (9,21,28,40). The goal of the present studies was to determine the potential role of intrarenal dopamine to modulate the effects of ANG II excess on renal function and development of progressive injury.…”
mentioning
confidence: 96%
“…Thus, dopamine and ANG II appear to serve counterregulatory functions in the kidney (5,15,16). In this regard, dopamine inhibits renal renin expression (38) and inhibits ANG II-mediated tubule function and AT 1 expression (9,21,28,40). The goal of the present studies was to determine the potential role of intrarenal dopamine to modulate the effects of ANG II excess on renal function and development of progressive injury.…”
mentioning
confidence: 96%
“…22 The lifetime of AT 1 R ͑-EGFP, the donor͒ is shortened to 1.68 ns with D 5 R stimulation, in the presence of ubiquitin as the acceptor fluorophore, suggesting that a fraction of AT 1 Rs is polyubiquitinated and processed for proteasomal degradation. 22 Our previous FRET studies showed that some of the internalized AT 1 Rs escape degradation and recycle back to the plasma membrane, coordinately, via Rab4 and Rab11 following Ang II stimulation. 26 In this study, Ang II treatment shortens the AT 1 R-EGFP lifetime, in the presence of Rab5, Rab7, and LAMP1 labeled with Alexa 555 ͑Table 2, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Utilizing these techniques, we reported recently that the AT 1 R is degraded in proteasomes on stimulation of the D 5 dopamine receptor ͑D 5 R͒ in human renal proximal tubule and HEK293 cells. 22 This is in contrast to the lysosomal degradation of AT 1 R on binding with its endogenous ligand, Ang II. 17,18 However, the dynamic regulation of AT 1 R degradation following Ang II stimulation is not well understood.…”
Section: Introductionmentioning
confidence: 98%
“…The fluorophore pairs (Invitrogen, Life Technologies) used for FRET imaging were Alexa Fluor 555 (the acceptor dipole) conjugated with D 1 R antibody and pIR-Alexa Fluor 488 (the donor dipole). Seven images were acquired for each FRET analysis with an Olympus Fluoview FV300 laser scanning confocal microscope equipped with a ϫ60/1.4 NA objective, an Argon (488 nm) and HeNe (543 nm) laser, emission filters of 515/50 nm, and a 590-nm long pass filter (28).…”
Section: Förster Resonance Energy Transfer (Fret) Microscopymentioning
confidence: 99%